Investigating the Possibility of Distributed Leadership in Schools in Cyprus: A Qualitative Case Study in a Public Upper Secondary School - Antoniou, Anna (2011)
This study is an attempt to investigate whether distributed leadership is developed in practise in Cypriot schools from the point of view of six people which are employed in a public upper secondary school. This particular school is involved in this study in order to shed some light on the wider situation in Cyprus.